Hepatitis A outbreak associated with kava drinking - Parker, Jo-Anne M; Kurien, Thomas Thompumkuzhiyil; Huppatz, Clare (Communicable Diseases Intelligence, 2014)
Hepatitis A is caused by the hepatitis A virus (HAV), with transmission occurring through the faecal-oral route. In May 2013, a case of hepatitis A infection was reported to a Western Australian regional public health unit, with infection acquired in Fiji. Following this, 2 further cases were linked to the index case by kava drinking and 1 further case was a household contact of a secondary case. This outbreak highlights that the preparation of kava drink and/or the use of a common drinking vessel could be a vehicle for the transmission of HAV. Commun Dis Intell 2014;38(1):E26–E28.